Effective antidiabetic and antioxidant fractions of Otostegia persica extract and their constituents. (August 2014) - Tofighi, Zahra; Alipour, Fatemeh; Hadavinia, Hormoz; Abdollahi, Mohammad; Hadjiakhoondi, Abbas; Yassa, Narguess
Abstract Context: Otostegia persica (Burm.) Boiss. (Lamiaceae), "Goldar" in Persian, is widely used in the folk medicine of south Iran for control of diabetes mellitus. Objective: In the present study, hypoglycemic and antioxidant effects of different fractions of the O. persica extract were investigated and constituents of effective fractions were elucidated. Materials and method: Different concentrations (100–400 mg/kg) of aqueous infusion (AI) of flowering aerial parts of the plant (traditional preparation) and all fractions of the O. persica extract (i.p. injection) were tested for antidiabetic activity in streptozocin-induced diabetic NMRI mice. Blood glucose level was measured at time 0 and intervals of 1, 2, 4, and 6 h later. Antioxidant activities of different fractions of the plant extract and pure compounds (0.1, 0.5, and 1 mg/ml) were determined with the DPPH method. Four compounds were isolated and identified from potent fractions. Results and discussion: Antidiabetic activity demonstrated that the effect of the methanol fraction at a dose of 300 mg/kg was equivalent with glibenclamide, and at a dose of 400 mg/kg was comparable with glibenclamide and insulin (p > 0.05). The EC50 of the methanol fraction was 307.12 mg. Methanol and ethyl acetate fractions showed antioxidant activities (both IC50 equal to 0.49 mg/ml), so these fractions were selected for the purification of compounds. Chrysoeriol from ethyl acetate and three apigenin derivatives (6-methylapigenin, apigenin-7-O-glucoside, and echinaticin) from the methanol fraction were isolated and identified (new for the species). Chrysoeriol exhibited potent antioxidant activity comparable with vitamin E and BHT (p > 0.05). Conclusion: The present study confirmed the folklore usage of O. persica for antidiabetic properties.